Wymiana spojrzeń. „Zaręczyny w San Domingo” Heinricha von Kleista na tle niemieckich badań postkolonialnych - Kledzik, Emilia (Wydawnictwo Naukowe UAM w Poznaniu, 2012)
The article reports on the state of research in the German postcolonial studies, comparing it with a discussion on the implementation of a similar project in the Polish literary discourse, and on the basis of the bibliography argues that German researchers boldly confront the traditional instruments of interpretation with those of postcolonial studies. The proof of this state is also presented on the basis of considerations of German researcher, Monica Ehlers, who gives the interpretation of the story of Heinrich von Kleist Betrothal in Santo Domingo. According to her view, the text anticipates the critical point of modernity, demonstrating crisis of the primacy of sight, which constitutes a discursive figure of European domination.
Exchange of views. Betrothal in Santo Domingo by Heinrich von Kleist on the background of German postcolonial studies